2017
DOI: 10.3791/54770
|View full text |Cite
|
Sign up to set email alerts
|

Film Extrusion of <em>Crambe abyssinica</em>/Wheat Gluten Blends

Abstract: Crambe abyssinica is a plant with potential for use in industrial (non-food) plant oil production. The side stream from this oil production is a high-protein crambe meal that has limited value, as it is not fit for food or feed use. However, it contains proteins that could potentially make it a suitable raw material for higher-value products. The purpose of this study was to find methods of making this side stream into extruded films, showing that products with a higher value can be produced. The study mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Thus, modeling these proteins is extremely difficult and requires a large amount of computer power. However, the storage proteins of cereals are highly useful and important: (i) as a storage resource for the plant to regenerate itself [7]; and (ii) for human [7] and animal [121] food and feed purposes; and are potentially useful in (iii) non-food applications, such as replacement of petroleum-based plastics [10,122]. A clear structure-function relationship has been demonstrated between the formation of protein structures during processing and the functionality of products produced from cereal storage proteins [123,124].…”
Section: Future Opportunities For Modeling Cereal Seed Storage Proteinsmentioning
confidence: 99%
“…Thus, modeling these proteins is extremely difficult and requires a large amount of computer power. However, the storage proteins of cereals are highly useful and important: (i) as a storage resource for the plant to regenerate itself [7]; and (ii) for human [7] and animal [121] food and feed purposes; and are potentially useful in (iii) non-food applications, such as replacement of petroleum-based plastics [10,122]. A clear structure-function relationship has been demonstrated between the formation of protein structures during processing and the functionality of products produced from cereal storage proteins [123,124].…”
Section: Future Opportunities For Modeling Cereal Seed Storage Proteinsmentioning
confidence: 99%
“…Thus, novel protein-based materials are of emerging importance. However, protein-based materials developed directly from the crambe meal have until now showed poor performance, although blends with wheat gluten have shown some promise. , The crambe seed shares the main storage protein groups of other brassicas, i.e., their proteins consist of cruciferin (12S globulin) and napin (2S albumin). , Previous studies on thermal processing of proteins from crambe have shown that cruciferin-rich fractions have a substantial ability to aggregate on heating, while the napin fraction is resistant to aggregation at a process temperature of 130 °C …”
Section: Introductionmentioning
confidence: 99%
“…Crambe oil from Crambe abyssinica plant fills these characteristics and is composed of different fatty acids, with specific properties, which are absent in other raw materials, being considered biocompatible and biodegradable [14,15]. Crambe abyssinica is a plant that can also provide a suitable raw material for higher-value products, such a, polymers, polymer additives, surfactants, personal care products and pharmaceuticals [16,17,18]. Castor oil is inherent biodegradable, of low cost, almost non-toxic, industrially [14,15] favorable, and easily available [19,20].…”
Section: Introductionmentioning
confidence: 99%